2018
DOI: 10.1002/arp.1593
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical correlation: global versus local perspectives

Abstract: Robust anomalies that point to the same buried features frequently occur in diverse data sets from multi‐method surveys [e.g. ground penetrating radar (GPR), magnetic gradiometry, electrical resistivity]. Relationships between such corresponding anomalies traditionally have been noted subjectively, through visual comparisons of mappings or overlays of geophysical results. These circumstances create a paradox because theory and correlational studies generally suggest largely independent dimensions, while mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…A major problem with these two approaches is given by the fact that the different physical quantities used to map the same archaeological features generate, in most cases, structural lineaments that are slightly displaced, with respect to each other, due to measurement errors, instrument sensitivity, etc. Consequently, these maps may display very low correlation, even when a buried object is characterized by significant contrasts of such different physical quantities [23]. To overcome this problem, it is possible to apply statistical methods of data integration, for example local Pearson [23] and principal component analysis [24].…”
Section: Integration Of Geophysical Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major problem with these two approaches is given by the fact that the different physical quantities used to map the same archaeological features generate, in most cases, structural lineaments that are slightly displaced, with respect to each other, due to measurement errors, instrument sensitivity, etc. Consequently, these maps may display very low correlation, even when a buried object is characterized by significant contrasts of such different physical quantities [23]. To overcome this problem, it is possible to apply statistical methods of data integration, for example local Pearson [23] and principal component analysis [24].…”
Section: Integration Of Geophysical Datasetsmentioning
confidence: 99%
“…Consequently, these maps may display very low correlation, even when a buried object is characterized by significant contrasts of such different physical quantities [23]. To overcome this problem, it is possible to apply statistical methods of data integration, for example local Pearson [23] and principal component analysis [24]. In any case, it is important to note that none of these techniques should be used to combine magnetic anomalies or vertical gradients of the total magnetic field intensity with grids that represent the distribution of a physical quantity in the ground.…”
Section: Integration Of Geophysical Datasetsmentioning
confidence: 99%
“…We also calculated the corresponding values of the Pearson correlation coefficient (Table 3), which measures the statistical relationship between two variables. In particular, this coefficient is appropriate for geophysical studies applied in archaeology to identify any correlations existing between datasets collected using different geophysical methods [15,33,34]. The obtained values of this coefficient show that the best correlation is between the ERT and GPR results and that the worst correlation corresponds to the GPR and magnetic results.…”
Section: Anomaly Correlationmentioning
confidence: 98%
“…We detailed the geological knowledge of the substrate in this zone to support the interpretation of geophysical methods. Currently, it is very common in archaeological studies to apply several geophysical methods to investigate anomalies that correspond to the same structure, because different methods may reveal different aspects of the subsurface [14][15][16][17]. In this study, we analysed the main anomalies revealed by each method and evaluated the graphical and numerical spatial correlation.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed concept is built upon the original work carried out by the Committee on Earth Observation Satellites (CEOS), which formulated the concept of virtual constellations, which was then extended by Wulder et al [16]. Although fusion and integration analysis of various remote sensing datasets have been reported in the past for archaeological research (see for instance [2,18,19,20,21,22,23], the concept of virtual constellations, proposed by CEOS is more than complementary observations. It is a framework for synergistic and coordinated use of earth observation sensors to increase the data availability, minimizing “unnecessary redundancy and costs” [16].…”
Section: Introductionmentioning
confidence: 99%